THE INFLUENCE OF DEFERRED TAX, TAX TO BOOK RATIO AND FIRM SIZE ON COMPANY PERFORMANCE - Rita Junita; Putri Dwi Wahyuni (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to investigate the influence of tax factors, namely deferred tax, tax to book ratio, and company size on the performance of companies in the mining sector listed on the Indonesia Stock Exchange. The research period covers 2020 to 2022, illustrating the dynamic economic conditions and regulatory changes in Indonesia. This research methodology will use a quantitative approach with secondary data analysis from the annual financial reports of companies listed on the Indonesia Stock Exchange. The analytical method used in this research is multiple linear regression with SPSS statistical testing tools. The results of this research are that deferred tax, tax to book ratio and company size have a significant effect on company performance.